Students' Perception of the English Teaching and Learning Process in ITB AAS Indonesia During the 2022/2023 Academic Year - Fitria, Tira Nur (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2024)
The study describes students' perceptions of the English teaching and learning process at ITB AAS Indonesia during the 2022/2023 academic year through descriptive qualitative research. The analysis reveals that English lecturers are responsible for delivering the syllabus and material for a semester of English learning, conveying the learning contract, and distributing books/modules. They also teach English using both offline and online methods, using institutional e-learning platforms like Zoom with Live YouTube. They provide learning materials weekly, discuss them with students, and provide summary/conclusion, assessment, reflection, feedback, and follow-up at the last meeting. In the ELT evaluation, lecturers provide English tasks, provide leeway for assignment collection, conduct mid-semester and final semester exams, offer opportunities for English follow-up exams, and explain the course value. These planning, implementation, and evaluation are crucial for improving the quality of educators, students, and educational institutions. In planning, it shows generally positive perception among students regarding the organization and facilitation of the English teaching and learning process at the beginning of the semester. In the implementation, it indicates a strong endorsement from students regarding various aspects of the English teaching and learning process at ITB AAS Indonesia. While in the evaluation, it indicates a positive perception among students regarding the organization and administration of assessments and tasks within the English teaching and learning process at ITB AAS Indonesia.